Computational Advances in Drug Safety: Systematic and Mapping Review of Knowledge Engineering Based Approaches - Natsiavas, Pantelis; Malousi, Andigoni; Bousquet, Cédric; Jaulent, Marie-Christine; Koutkias, Vassilis (Frontiers in Pharmacology, 2019)
Drug Safety (DS) is a domain with significant public health and social impact. Knowledge Engineering (KΕ) is the Computer Science discipline elaborating on methods and tools for developing “knowledge-intensive” systems, depending on a conceptual “knowledge” schema and some kind of “reasoning” process. The present systematic and mapping review aims to investigate KE-based approaches employed for DS and highlight the introduced added value as well as trends and possible gaps in the domain. Journal articles published between 2006 and 2017 were retrieved from PubMed/MEDLINE and Web of Science® (873 in total) and filtered based on a comprehensive set of inclusion/exclusion criteria. The 80 finally selected articles were reviewed on full-text, while the mapping process relied on a set of concrete criteria (concerning specific KE and DS core activities, special DS topics, employed data sources, reference ontologies/terminologies and computational methods, etc.). The analysis results are publicly available as online interactive analytics graphs. The review clearly depicted increased use of KE approaches for DS. The collected data illustrate the use of KE for various DS aspects, such as Adverse Drug Event (ADE) information collection, detection and assessment. Moreover, the quantified relation of using KE for the respective DS core activities highlighted room for intensifying research on KE for ADE monitoring, prevention and reporting. Finally, the assessed use of the various data sources for DS special topics demonstrated extensive use of dominant data sources for DS surveillance, i.e. Spontaneous Reporting Systems, but also increasing interest in the use of emerging data sources, e.g. observational healthcare databases, biochemical/genetic databases and social media. Various exemplar applications were identified with promising results, e.g. improvement in ADR prediction, detection of drug interactions and novel ADE profiles related with specific mechanisms of action, etc. Nevertheless, since the reviewed studies mostly concerned proof-of-concept implementations, more intense research is required to increase the maturity level that is necessary for KE approaches to reach routine DS practice. In conclusion, we argue that efficiently addressing DS data analytics and management challenges in order to establish a continuous learning DS system, requires the introduction of high-throughput KE-based methods for effective knowledge discovery and management.